Social Sustainability and Volunteering: Broader Contextual Understandings of the Challenges and Solutions - Tye, Marian; Costello, Diane (2015)
Advocating for socially inclusive perspectives of volunteering, the United Nations Volunteering Report called for broader understandings to inform the field’s limited theoretical notions of volunteerism. In Australia, awareness of the inadequacy of organizational management perspectives of volunteering to respond to the diverse policy needs of the context is also strong. Volunteering in Australia, particularly the sport sector has played a critical role in the establishment and survival of communities, especially rural and remote parts of the nation. There is however, a paucity of research that captures the broader issues underpinning volunteering within the community sport sector, particularly the social sustainability implications. Undertaking broader research parameters, this formative qualitative study draws on volunteer narratives gained from six community sports contexts spanning diverse socio-economic and geographic contexts in Western Australia (WA). A key revelation is that the issues are context based and more innovative policy solutions that go beyond organizational management perspectives are vital to promote the social sustainability of the community sport sector.